2008
DOI: 10.1128/aac.00689-07
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Meropenem with and without Ciprofloxacin and Colistin against Pseudomonas aeruginosa and Acinetobacter baumannii

Abstract: Time-kill synergy studies showed that at 24 h, subinhibitory meropenem and ciprofloxacin concentrations of 0.06 to 128 and 0.03 to 32 g/ml, respectively, showed synergy against 34/51 Pseudomonas aeruginosa strains; subinhibitory concentrations of meropenem (0.06 to 8 g/ml) and colistin (0.12 to 1 g/ml) showed synergy against 13 isolates. Subinhibitory meropenem and ciprofloxacin concentrations of 0.25 to 2 and 0.12 to 16 g/ml, respectively, showed synergy against 18/52 Acinetobacter baumannii strains at 24 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
52
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 25 publications
4
52
0
2
Order By: Relevance
“…22,24,25 Colistin activity can be enhanced when combined with antibiotics with different action as carbapenems, rifampicin, ceftazidime. 26,27,28 Present study observd 50% synergism, 30% additive effect, 20% indifference while combining colistin with imipenem. In accordance with the present study Souli et al 29 reported 56.3% synergism and 43.7% indifference.…”
Section: Discussionmentioning
confidence: 99%
“…22,24,25 Colistin activity can be enhanced when combined with antibiotics with different action as carbapenems, rifampicin, ceftazidime. 26,27,28 Present study observd 50% synergism, 30% additive effect, 20% indifference while combining colistin with imipenem. In accordance with the present study Souli et al 29 reported 56.3% synergism and 43.7% indifference.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we reported the prevalence of colistin-resistant isolates (67% of K. pneumoniae) in Tamil Nadu (15), however, to the best of our knowledge, this is the first report on the prevalence of class 1 integrons in colistin-resistant K. pneumoniae in the Southern part of India. The selection of antibiotics colistin-meropenem for the analysis of in vitro combination therapy was based on the phenotypic studies, and chosen antibiotics have differed in mechanism and in the site of action (25,26). Antibiotic combinations of colistin plus rifampin (23), ertapenem plus doripenem (27), tigecycline plus colistin, fosfomycin plus meropenem, and colistin plus carbapenem (imipenem, meropenem) were extensively studied against colistin resistant Klebsiella pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Killing curves utilizing meropenem, gentamicin, or meropenem plus gentamicin were performed as previously described (8). Briefly, tubes containing cation-supplemented Mueller-Hinton broth with antibiotics at concentrations equal to the MICs of the isolates were seeded with a log-phase bacterial inoculum of 5 ϫ 10 6 CFU/ml (14) and incubated in a shaking water bath at 37°C. Samples (50 l) of this broth culture were removed after 1, 3, 6, 9, 12, and 24 h for enumeration of viable bacteria by serial dilution and plating on antibiotic-free Mueller-Hinton agar plates.…”
mentioning
confidence: 99%
“…The analysis was performed three times for all isolates; the mean values of viable CFU were estimated and plotted on a semilogarithmic graph, and a 24-h time-kill curve was constructed for each isolate. Bactericidal activity (99.9% killing) was defined as a Ն3 log 10 CFU/ml reduction in viable cell counts with respect to the original inoculum (12,14).…”
mentioning
confidence: 99%